Agama dan Kepemimpinan Nasional - Suparno, Paul (Unisia, 2016)
All of Indonesian leaders are the faith people, and the former president Stewart is a worship person. On the contrary, they can not solve the problems of this nation, and one of them, has decided and conducted the policies that supporting the process of destruction of indonesian progress so that those policies caused long crisis up to now. Indonesian faces the problem of corruption, social cinflict, human rights, law enforcement etc. According to author of this article, it is clear that Indonesia is democracy state, for that reason, the leader that expected is the leader who has higfh morality and a brave to against corruption, to build Indonesian unity, to appreciate human rights etc.